Interface Engineering of MoS2/Ni3S2 Heterostructures for Highly Enhanced Electrochemical Overall‐Water‐Splitting Activity. (21st April 2016) - Zhang, Jian; Wang, Tao; Pohl, Darius; Rellinghaus, Bernd; Dong, Renhao; Liu, Shaohua; Zhuang, Xiaodong; Feng, Xinliang
Abstract: To achieve sustainable production of H2 fuel through water splitting, low‐cost electrocatalysts for the hydrogen‐evolution reaction (HER) and the oxygen‐evolution reaction (OER) are required to replace Pt and IrO2 catalysts. Herein, for the first time, we present the interface engineering of novel MoS2 /Ni3 S2 heterostructures, in which abundant interfaces are formed. For OER, such MoS2 /Ni3 S2 heterostructures show an extremely low overpotential of ca. 218 mV at 10 mA cm −2, which is superior to that of the state‐of‐the‐art OER electrocatalysts. Using MoS2 /Ni3 S2 heterostructures as bifunctional electrocatalysts, an alkali electrolyzer delivers a current density of 10 mA cm −2 at a very low cell voltage of ca. 1.56 V. In combination with DFT calculations, this study demonstrates that the constructed interfaces synergistically favor the chemisorption of hydrogen and oxygen‐containing intermediates, thus accelerating the overall electrochemical water splitting.